2016
DOI: 10.1016/j.jpeds.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Optimized Breastfeeding on the Costs of Necrotizing Enterocolitis in Extremely Low Birthweight Infants

Abstract: Objective To estimate risk of NEC for ELBW infants as a function of preterm formula and maternal milk (MM) intake and calculate the impact of suboptimal feeding on NEC incidence and costs. Design We used adjusted odds ratios (aORs) derived from the Glutamine Trial to perform Monte Carlo simulation of a cohort of ELBW infants under current suboptimal feeding practices, compared to a theoretical cohort in which 90% of infants received at least 98% MM. Results NEC incidence among infants receiving ≥98% MM was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 39 publications
(52 reference statements)
0
38
1
2
Order By: Relevance
“…Multiple retrospective and prospective randomized trials have demonstrated the beneficial effect of breast milk feeding on reducing the risk for NEC in preterm infants 33-38 . In a secondary analysis of the NICHD glutamine trial, Colaizy et al 5 determined a 12-fold increased risk of NEC associated with exclusive formula feeding compared with exclusive breast milk feeding in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple retrospective and prospective randomized trials have demonstrated the beneficial effect of breast milk feeding on reducing the risk for NEC in preterm infants 33-38 . In a secondary analysis of the NICHD glutamine trial, Colaizy et al 5 determined a 12-fold increased risk of NEC associated with exclusive formula feeding compared with exclusive breast milk feeding in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast milk has been shown to be protective against NEC 4, 5 , postnatal antibiotic exposure may increase the risk for NEC 6, 7 . Intestinal barrier immaturity is the proximate cause of susceptibility to NEC in preterm neonates 8, 9 , but few preterm infants <30 wk gestation have been included in prior studies of intestinal permeability (IP) 10-15 and the impact of current feeding practices and antibiotic exposures on intestinal barrier maturation in the extremely preterm population is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, early exclusive breast milk feeding and low antibiotic exposure was associated with the presence of members of Clostridiales in the stool microbiota of preterm infants. We have previously observed these two factors are associated with improved IP in preterm infants 16 , which has been shown to be critically protective against NEC 35 . This observation emphasizes the importance of factors such as clinical administration of nutritional supplement and limiting exposure to antibiotic in neonatal care units.…”
Section: Discussionmentioning
confidence: 85%
“…Our calculations modeled the potential health savings associated with reaching Healthy People 2020 breastfeeding objectives, assuming that increasing access to lactation support services for low-income mothers will significantly improve breastfeeding rates. These ambitious assumptions are grounded in models used both nationally (Bartick & Reinhold, 2010; Colaizy et al, 2016) and by other states (Ma et al, 2013), as well as in evidence from previous interventions showing the effectiveness of IBCLC services for increasing exclusive breastfeeding and breastfeeding intensity in low-income populations (Bonuck et al, 2014; Su et al, 2007). …”
Section: Discussionmentioning
confidence: 99%